Puzzling out a palimpsest: Testing an interdisciplinary study in level O of Abric Romaní. (28th September 2016) - Bargalló, Amèlia; Gabucio, Maria Joana; Rivals, Florent
Abstract: Cultural deposits, especially those accumulated in caves and rock shelters, are usually the results of several occupational events in the same space, forming palimpsests. In addition, the materials of these occupational events tend to be deposited along with remains of natural origin and may be altered, partially destroyed or reworked due to the process of superimposition. The work presented here focuses on dissecting the palimpsest of level O at Abric Romaní through an interdisciplinary analysis. We analyzed a particular area, located in the northeastern corner of the site. This work is based on the study of the lithic and faunal remains recovered in this area, with the aim of dissecting the palimpsest into the smallest possible units. To do this, we used different methods and techniques including archaeostratigraphy, intra-site spatial archaeology, zooarchaeology, tooth microwear, taphonomy, lithic technology, and faunal and lithic refits. These methods allowed us to identify two archaeolevels in this area (Oa and Ob). Oa comprises a maximum of three accumulations and Ob holds two accumulations of archaeological remains. These accumulations are generally related to combustion structures. Based on the results obtained from zooarchaeological, taphonomic and lithic technology analyses, we characterized each accumulation. The analysis of the lithic and faunal refits helped to identify synchronic and diachronic links. After having processed all of the results, we were able to interpret the intra-area organization and its role in relation to the rest of the site. Our results have shown that it is possible to obtain high-resolution data for dissecting a palimpsest using different methodologies. It is, however, important to remember that although we were able to distinguish these finer units, we were still working with palimpsests. Nevertheless, the study of these finer units makes it possible to work with time scales that are closer to ethnographic time, thereby facilitating further ethno-archaeological interpretation.